2017
DOI: 10.20960/nh.460
|View full text |Cite
|
Sign up to set email alerts
|

Iodine levels are associated with oxidative stress and antioxidant status in pregnant women with hypertensive disease

Abstract: Background: Previously has been reported the antioxidant function of iodine, and iodine deficiency as a risk factor of preeclampsia.Aim: We analyze the association between iodine deficiency, oxidative stress and antioxidant status with hypertensive disease of pregnancy (HPD).Method: 57 pregnant women were recruited in the last trimester of pregnancy, 20 diagnosed with hypertensive disease of pregnancy and 37 normotensive pregnant women. Urinary iodine concentration (UIC), TSH, free T4 (fT4), total antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
1
28
2
Order By: Relevance
“…Firstly, since patients with thyroid nodular goiter often have concurrent thyroid antibodies, iodine deficiency thus may indirectly increase the TAI prevalence by increasing the prevalence of thyroid nodular goiter and causing damages to thyroid tissues (17,66,67,68,69). In addition, several studies have found that iodine can contribute to redox balance and iodine deficiency increases the degree of oxidative stress which may further promote immune response and increase autoimmune attack (70,71,72). Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, since patients with thyroid nodular goiter often have concurrent thyroid antibodies, iodine deficiency thus may indirectly increase the TAI prevalence by increasing the prevalence of thyroid nodular goiter and causing damages to thyroid tissues (17,66,67,68,69). In addition, several studies have found that iodine can contribute to redox balance and iodine deficiency increases the degree of oxidative stress which may further promote immune response and increase autoimmune attack (70,71,72). Finally, TSH level is intensively related to iodine status, and iodine deficiency can result in increased TSH level (17,73).…”
Section: Discussionmentioning
confidence: 99%
“…The diverse functions of iodine include bactericidal activity and apoptosis induction, and it is involved in trophoblast migration, invasion, and differentiation. As an antioxidant, iodine may act directly as an electron donor and compete for binding sites with free radicals [ 77 ]. Iodine deficiency remains a significant health problem worldwide and affects both industrialized and developing nations [ 78 ].…”
Section: Nutrients Involved In Mitochondrial Function During Pregnmentioning
confidence: 99%
“…Mild iodine deficiency has been associated with increased oxidative stress and decreased total antioxidant capacity and SOD activity in pregnant women in Mexico [ 79 ]. It has also been reported that 70% of women with hypertensive disease in pregnancy were iodine deficient [ 77 ]. Mild iodine deficiency was an independent risk factor for gestational diabetes mellitus [ 80 ].…”
Section: Nutrients Involved In Mitochondrial Function During Pregnmentioning
confidence: 99%
“…In a small sample of 74 women, there was decreased total antioxidant status and superoxide dismutase activity in women with mild iodine deficiency in the 2nd and 3rd trimesters of pregnancy compared to pregnant women with optimal iodine levels [138]. Iodine sufficient pregnant women, as indicated by more than 150 micrograms per litre urinary iodine concentration, had higher superoxide dismutase enzyme activity compared to iodine-deficient pregnant women [66]. In vitro studies support this and have shown that iodine supplementation reduces ROS production in a dose-dependent manner [139].…”
Section: Iodine and Pregnancy Complicationsmentioning
confidence: 88%
“…Importantly, several studies have shown that iodine-deficient pregnant women are at an increased risk of pregnancy complications such as maternal high blood pressure, PE, IUGR and PTB [64][65][66]138,144,145] (Table 3). Iodine assessment methods can significantly impact the iodine measurement [146].…”
Section: Iodine and Pregnancy Complicationsmentioning
confidence: 99%